Kreatifitas Pengrajin Dalam Pengembangan Kerajinan Bambu Desa Selaawi Kecamatan Garut - Sandi Rediansyah; Wanda Listiani; Dinda Satya Upaja Budi (PANTUN: Jurnal Ilmiah Seni Budaya, 2022)
Bamboo crafts in Garut area, more precisely in Selaawi District, are a picture of empowering surrounding natural products to become something playing a very important role for Selaawi community. In addition to being used for personal needs, bamboo is also a source of livelihood for the surrounding community. The bamboo craft which becomes the pride of Selaawi people is a large bird cage. Some of the things becoming a problem in this study are how big the influence on the development of the shape and variety of lampshade decorations, both from the outside community and from the people of Selaawi Region itself. This study uses qualitative methods with interviews. The data analysis is conducted inductively from important themes to common themes. The expected contribution of this study is to encourage the creativity of the craftsmen to create a new and diverse form of crafts. Moreover, it is significant to introduce bamboo handicrafts to the wider community as a characteristic or identity originating from Selaawi District Region.Keywords: Selaawi, Bamboo Crafts, Decorative Lamp Covers, Creativity ABSTRAKKerajinan bambu di daerah Garut, lebih tepatnya di Kecamatan Selaawi merupakan gambaran pemberdayaan hasil alam yang ada di sekitar menjadi sesuatu yang sangat berperan penting untuk masyarakat Selaawi. Bambu selain dimanfaatkan untuk keperluan pribadi juga menjadi salah satu mata pencaharian bagi masyarakat sekitar. Kerajinan bambu yang menjadi suatu kebanggaan masyarakat Selaawi ialah sangkar burung yang berukuran besar. Beberapa hal yang menjadi masalah pada kajian ini adalah seberapa besar pengaruh terhadap pengembangan bentuk dan ragam hiasan tutup lampu, baik dari masyarakat luar maupun dari masyarakat Daerah Selaawi itu sendiri. Penelitian ini menggunakan metode kualitatif dengan wawancara. Kemudian analisis data secara induktif dari tema-tema yang penting ke tema yang biasa, serta mengartikan makna dari data. Hasil yang diharapkan pada kajian ini ialah kreativitas para pengrajin ini menjadi modal utama dalam menciptakan suatu kerajinan bentuk baru dan beragam sekaligus memperkenalkan kerajinan bambu ke masyarakat luas sebagai ciri khas atau identitas yang berasal dari Daerah Kecamatan Selaawi.